2021
DOI: 10.1111/den.13964
|View full text |Cite
|
Sign up to set email alerts
|

Combined endocytoscopy with pit pattern diagnosis in ulcerative colitis‐associated neoplasia: Pilot study

Abstract: Objectives: Ulcerative colitis-associated neoplasias (UCAN) are often flat with an indistinct boundary from surrounding tissues, which makes differentiating UCAN from non-neoplasias difficult. Pit pattern (PIT) has been reported as one of the most effective indicators to identify UCAN. However, regenerated mucosa is also often diagnosed as a neoplastic PIT. Endocytoscopy (EC) allows visualization of cell nuclei. The aim of this retrospective study was to demonstrate the diagnostic ability of combined EC irregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Their data found that both pit patterns and its combination with endocytoscopy had high sensitivities to diagnose UC-associated neoplasia (97.8% vs 100%). In addition, the authors also demonstrated that the specificity was higher in the combined assessment of pit patterns with endocytoscopy compared to pit patterns alone (84.4% vs 57.5%) (Table 1 )[ 26 ]. This study demonstrated that endocytoscopy can enhance the specificity of pit patterns for the diagnosis of neoplasia in IBD patients, suggesting an endocytoscopy-assisted pit pattern assessment may be a novel approach to overcome the limitation of pit patterns alone.…”
Section: Utility Of Endocytoscopy For Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Their data found that both pit patterns and its combination with endocytoscopy had high sensitivities to diagnose UC-associated neoplasia (97.8% vs 100%). In addition, the authors also demonstrated that the specificity was higher in the combined assessment of pit patterns with endocytoscopy compared to pit patterns alone (84.4% vs 57.5%) (Table 1 )[ 26 ]. This study demonstrated that endocytoscopy can enhance the specificity of pit patterns for the diagnosis of neoplasia in IBD patients, suggesting an endocytoscopy-assisted pit pattern assessment may be a novel approach to overcome the limitation of pit patterns alone.…”
Section: Utility Of Endocytoscopy For Ibdmentioning
confidence: 99%
“…This study demonstrated that endocytoscopy can enhance the specificity of pit patterns for the diagnosis of neoplasia in IBD patients, suggesting an endocytoscopy-assisted pit pattern assessment may be a novel approach to overcome the limitation of pit patterns alone. However, they also found that the specificity can be affected by active inflammation (Mayo endoscopic subscore 2-3) and that false positive rates were high (16.2% in type II-V pits with positive irregularly-formed nuclei and 10.3% in type V)[ 26 ]. Therefore, achieving endoscopic remission is essential for an accurate evaluation of pit-patterns or cellular nuclei using magnifying scopes.…”
Section: Utility Of Endocytoscopy For Ibdmentioning
confidence: 99%
“…Some prototype endocytoscopes have been reported; however, commercially available endocytoscopes for the upper and lower gastrointestinal tract (GIF-H290EC and CF-H290ECI; Olympus Corp. Tokyo, Japan) were launched in 2018. 4,5 These two scopes have one objective lens with 520-fold magnification and a manual zoom mechanism similar to a conventional magnifying endoscope. One endoscope can switch from normal observation to magnified observation and ultra-magnifying observation.…”
Section: Specification Of Endocytoscopes and Standard Observation Techniquesmentioning
confidence: 99%
“…2. Endocytoscopic classification for colorectal lesions, proposed by Kudo et al 5 Their classification is based on the structure of the crypts and the shape of the nuclei.…”
Section: Ec For the Duodenummentioning
confidence: 99%
See 1 more Smart Citation